2006
DOI: 10.1021/ja0631605
|View full text |Cite
|
Sign up to set email alerts
|

pH Responsiveness of Dendrimer-like Poly(ethylene oxide)s

Abstract: Poly(ethylene oxide) (PEO) and poly(acrylic acid) (PAA), two polymers known to form pH-sensitive aggregates through noncovalent interactions, were assembled in purposely designed architecture -a dendrimer-like PEO scaffold carrying short inner PAA chains-to produce unimolecular systems that exhibit pH responsiveness. Because of the particular placement of the PAA chains within the dendrimer-like structure, intermolecular complexation between acrylic acid (AA) and ethylene oxide (EO) units-and thus macroscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 35 publications
0
94
0
Order By: Relevance
“…PEG (6) and PEG (7). In order to avoid this dimer formation and to synthesize PEG with protected thiol end groups, a two-step synthesis was adopted.…”
Section: H-nmr (Simentioning
confidence: 99%
“…PEG (6) and PEG (7). In order to avoid this dimer formation and to synthesize PEG with protected thiol end groups, a two-step synthesis was adopted.…”
Section: H-nmr (Simentioning
confidence: 99%
“…This includes copolymers with polystyrene cores and a corona of poly(ethylene oxide) [50] or poly(tert-butyl acrylate)/poly(acrylic acid) [51,52] chains, copolymers derived from poly(ethylene oxide) cores with poly(tert-butyl acrylate)/poly(acrylic acid) segments in their corona [53], as well as more complex structures such as dendrimer-like poly(ethylene oxide) containing up to 48 poly(ethylene oxide) segments on the outside and 21 side-chains of poly(tert-butyl acrylate)/poly(acrylic acid) covalently bonded to the branch junctions of the preceding generations [54]. The self-assembly of some of the tert-butyl acrylate copolymers was investigated by the Langmuir force balance technique [51,52], while dynamic light scattering measurements in aqueous solutions showed that the copolymers with poly(acrylic acid) segments grafted at the branch junctions displayed pH-dependent size variations depending on the degree of ionization of the polyelectrolyte segments [54].…”
Section: Methodsmentioning
confidence: 99%
“…dendrimers [21]. These molecules can be made in different sizes, even nano-sizes, and they can be spherical or have other 3D structures.…”
Section: Future Scope Of Sensors In Membrane Process Characterizationmentioning
confidence: 99%